Targeted deletion of nicotinamide adenine dinucleotide phosphate oxidase 4 from proximal tubules is dispensable for diabetic kidney disease development. Issue 6 (24th December 2020) - Thallas-Bonke, Vicki; Tan, Sih Min; Lindblom, Runa S; Snelson, Matthew; Granata, Cesare; Jha, Jay Chandra; Sourris, Karly C; Laskowski, Adrienne; Watson, Anna; Tauc, Michel; Rubera, Isabelle; Zheng, Guoping; et al.
Abstract: Background: The nicotinamide adenine dinucleotide phosphate oxidase isoform 4 (Nox4) mediates reactive oxygen species (ROS) production and renal fibrosis in diabetic kidney disease (DKD) at the level of the podocyte. However, the mitochondrial localization of Nox4 and its role as a mitochondrial bioenergetic sensor has recently been reported. Whether Nox4 drives pathology in DKD within the proximal tubular compartment, which is densely packed with mitochondria, is not yet known. Methods: We generated a proximal tubular–specific Nox4 knockout mouse model by breeding Nox4 flox/flox mice with mice expressing Cre recombinase under the control of the sodium–glucose cotransporter-2 promoter. Subsets of Nox4 ptKO mice and their Nox4 flox/flox littermates were injected with streptozotocin (STZ) to induce diabetes. Mice were followed for 20 weeks and renal injury was assessed. Results: Genetic ablation of proximal tubular Nox4 (Nox4 ptKO ) resulted in no change in renal function and histology. Nox4 ptKO mice and Nox4 flox/flox littermates injected with STZ exhibited the hallmarks of DKD, including hyperfiltration, albuminuria, renal fibrosis and glomerulosclerosis. Surprisingly, diabetes-induced renal injury was not improved in Nox4 ptKO STZ mice compared with Nox4 flox/flox STZ mice. Although diabetes conferred ROS overproduction and increased the mitochondrial oxygen consumption rate, proximal tubular deletion of Nox4 did not normalize oxidative stress or mitochondrial bioenergetics. Conclusions: Taken together, these results demonstrate that genetic deletion of Nox4 from the proximal tubules does not influence DKD development, indicating that Nox4 localization within this highly energetic compartment is dispensable for chronic kidney disease pathogenesis in the setting of diabetes.